AB0972 Utility of The Ultrasound for The Evaluation of Activity in Patients with Rheumatoid Arthritis in Remission or Low Clinical Activity in Treatment with Biological in Optimization Phase. (15th July 2016) - Martínez Pérez, R.; Rubio, E.; Fernández Alba, M.D.; Hernández, B.; Menor, R.; Povedano, J.
Abstract : Background: In rheumatoid arthritis (RA), the activity is correlated with radiological damage. Our therapeutic goal is clinical remission. The concept of clinical remission may be insufficient due to persistent subclinical inflammation, which can be determined by ultrasound. Objectives: Our goal is to determine the frequency of subclinical synovitis by ultrasonography in patients with RA in low activity or remission of the disease measured by CDAI, in biological treatment optimization phase. Methods: Transversal and longitudinal study describing the ultrasonographic changes in gray scale and Doppler in parallel with blind clinical evaluation. We included 23 patients (16 women and 7 men) with RA according to ACR criteria/EULAR under low activity/remission measured by CDAI, under biological treatment and optimized at least for 6 months. They were sent by their usual clinician, making a random selection. They were evaluated in the same day by a rheumatologist and blind sonographer. VAS, VGP, VGM, HAQ, number joints painful, joints swelling, ESR, CRP and CDAI were evaluated. Regarding the ultrasound, were evaluated; Synovitis and Doppler in 12 joints (wrists, second to fifth MCF and fifth bilateral MTF). Results: All patients were in low activity/remission in accordance with their rheumatologist. The baseline characteristics and different variables are described in Table 1 B, 1B. After the blind rheumatologist evaluation, the percentage of patients in remission/low activity was lower, 65.2% (15 patients, 2 in remission, 13 in low activity), p<0.005 compared to regular clinician. 8 patients had CDAI >10. The presence of subclinical synovitis in ultrasound was 69.6% (16 patients) with an average of 2.02± 1.9 of joints and 15 patients with Doppler. Therefore, only the 47.8% (11) of patients in remission/low activity was classified, compared to 100% and 65.2% of the regular and blind clinical respectively. 14 of the 23 patients were under optimization dose for 6–8 months, while 9 of them exceeded the 8 months. No differences were observed in the clinical status of both groups. Conclusions: Our study shows how the exploration performed by a rheumatologist blind to the patient's clinical situation brings a lower percentage of remission compared to outpatient valuation. As well, with the ultrasound we can observe a greater sensitivity for the detection of the disease than with physical examination. The detection of subclinical joint damage is often undertreated, showing ultrasound as a noninvasive technique of great help reducing joint damage. Disclosure of Interest: R. Martínez Pérez Grant/research support from: Abbvie, Phizer, Roche, E. Rubio Grant/research support from: Abbvie, Phizer, Roche, M. D. Fernández Alba Grant/research support from: Abbvie, Phizer, Roche, B. Hernández: None declared, R. Menor: None declared, J. Povedano: None declared